Evaluation of an oestrus synchronization protocol in sheep with temporary weaning for artificial insemination at fixed time - Espinoza Molina, Saúl (2020)
The research aimed to evaluate a protocol of induction of oestrous in lactating ewes with hormonal treatment of progestins and eCG with temporary weaning of lambs for artificial insemination at a fixed time by transcervical route using refrigerated semen on the presentation of oestrous and pregnancy and lambing rate. In total, 37 ewes were distributed among three treatments: T1, lactating ewes with temporary weaning (n=15); T2, lactating ewes with lamb at foot (n=10); T3, dry ewes without lamb (n=12). Temporary weaning was for 48 h prior to insemination. T1 and T3 presented a higher rate of manifest oestrous (100 and 91.66%, respectively) than T2 (60%; p<0.05). The non-return heat rate at 14-17 days post-service was statistically similar between groups (93.33, 60.0, 91.66% for T1, T2 and T3, respectively). Similarly, the pregnancy percentage by ultrasound at 45 days and the percentage of lambing showed similar values and were statistically similar (93.33, 60.0 and 66.67 and for T1, T2 and T3, respectively).